Older people and the smart city – Developing inclusive practices to protect and serve a vulnerable population - Aaro Tupasela; Juanita Devis Clavijo; Marjut Salokannel; Christoph Fink (Internet Policy Review)
Despite increased interest in the development of smart cities and urban spaces that cater to the needs of their inhabitants, there is a significant lack of information and experience when it comes to working with older people. URBANAGE is a European H2020 project focused on supporting urban planners and policymakers in the decision-making process for age-friendly cities by developing new technologies for evidence-based decision-making. Older adults over 60 years of age, public servants and other relevant stakeholders were invited to co-create and test the solution to ensure that their needs and challenges were being addressed by the project. Decision-makers are facing major challenges in terms of understanding and addressing the needs of vulnerable population groups, such as older people, because of the lack of large enough datasets of disaggregated anonymised data. In this article, we report on the main challenges encountered during the implementation of the URBANAGE project, and the development of the components for big data analytics, visualisations, predictive algorithms and simulation. Using examples from three European locations – Helsinki, Flanders and Santander – we describe and discuss how we can gather personal data related to the daily lives of older people in terms of the existing privacy and data protection laws in the EU. The use of new technologies, such as location-based information devices, can provide up-to-date and precise information regarding problems that older people face while moving around the city, but they pose privacy concerns at the same time.